Value creation and identity in cross-organizational communities of practice: A learner's perspective - Mavri, Aekaterini; Ioannou, Andri; Loizides, Fernando (My University, 2021)
The goal of this work is to evaluate the worth of learning, that resulted from student participation in a cross-organizational (industry-academia) Community of Practice (CoP). CoPs are groups of people who share common interest in a field and connect to co-create knowledge and competence within that. In this study, the CoP was integrated in a Higher Education Design course that was following a blended-learning approach. Internal and external collaboration was primarily facilitated through online technologies. The study employs the Value Creation framework to analyze the types and value of co-created learning and explores these results to draw inferences as to the effects of CoP participation on the learners' identities, which were continuously being reformulated. The resulting CoP interactions indicated a strong immediate learning value. These also generated new insights (potential value) and familiarized learners with the characteristics of the real-world practice. The effective transfer of knowledge into the academic practice was confirmed by the significant improvements in student performances (applied & realized value). Finally, CoP participation steered a shift in learner perspectives, by pragmatically transforming their perception of achievement and orientating them towards transitioning and evolving in the professional sphere (reframed value).
Keywords: Communities of practice; Cross-organizational; Value creation; Identity; Creativity; Collaborative technologies; Real-world relevance